Student Motivation on Gap Year: Focus Group Study - Yee, Yip Foon (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed to explore the factors that motivate college students to take a gap year before they enroll in college. Qualitative research using focus group methodology was used in this exploratory research. The content analysis method was used to analyze the transcribed data. The data analysis procedure resulted in five factors, namely: (i) money; (ii) interpersonal relations; (iii) work experience; (iv) growth opportunities; and (v) break from academic; all of which have influenced college students to take a gap year. Overall, the results of this study add to the literature of gap year for education in Malaysia. This study also provides valuable information to the administrators or the Ministry of Higher Education, which would help them design a better gap year program.